Relationship Analysis of Interpersonal Support with Well-being Index Among University Students - Kaur, Rajinder; Sharma, Seema (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted August to December, 2019 under the Department of Human Development and Family Studies, College of Community Science, Punjab Agricultural University, Ludhiana, Punjab, India to assess the relationship between the well-being index and interpersonal support among university students i.e. Guru Nanak Dev University, Amritsar (GNDU), Punjab Agricultural University, Ludhiana (PAU) and Punjabi University, Patiala (PUP). The sample consisted of 480 students from the science stream studying in the 1st and 2nd years of the undergraduate program. The sample consisted of an equal number of first-year students (n=80) and second-year students (n=80) from each university. Random sampling was done to draw samples from three purposively selected universities. The study’s objective was to assess the relationship between the well-being index and interpersonal support of university students. The well-being index and the Interpersonal support scale were used as data collection tools to evaluate the well-being index and available interpersonal support among university students. Statistical tools were used to analyse the data. The results revealed that all the dimensions of the well-being index were positively related to interpersonal support year-wise, gender-wise, and overall universities-wise. Those students who perceived higher levels of interpersonal support also tended to have higher levels of well-being across various dimensions. The study will be helpful for the youth to understand the importance of interpersonal support and its relationship with the well-being index. University students who perceived better social support networks tend to have higher levels of well-being compared to those who lack such support.